Korelasi Antara Hasta Brata (Konsep Keemimpinan dalam Perspektif Budaya Jawa) dan Islamic leadership (Konsep Kepemimpinan dalam perspektif Islam) - Hamim, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2014)
Leadership is a process when one directs, guides, affects or control the thoughts,feelings, or behavior of others. It is obvious that leadership is oneâ€™s action orperformance that causes someone else or a group moves toward specific purposes.There are three things that need to be distinguished, the leader, leadership andleading. The position of â€œleaderâ€ is a role in a particular system. Those in aformal role do not necessarily have the leadership skills and not necessarily ableto lead. Leadership, is basically related to oneâ€™s skills, expertise, and level ofpower. Leadership can be owned by people who are not â€œleadersâ€. Leadershipability affects others in various ways, while leading is the result of the use ofoneâ€™s role. The leadership concept in the perspective of Javanese and Islam isexplored in this article.